Environmental and Spatial Drivers of Latrine Site Selection in Dorcas Gazelle - Marouane Louhichi; Marie Petretto; Olfa Tabel Hmidi; Kamel Dadi; Ali Zaidi; Mohsen Jarray; Mohsen Chammem (Ecology and Evolution)
ABSTRACT The dorcas gazelle (Gazella dorcas Linnaeus, 1788), a vulnerable and cryptic species, has experienced significant population declines in recent decades. Its survival now hinges on robust conservation efforts within protected areas. However, the species' elusive nature complicates direct observation, underscoring the need for innovative and adaptive conservation approaches. In this study, we utilised latrine mapping, a cost‐effective and non‐invasive method, to evaluate the spatial dynamics and habitat preferences of dorcas gazelles in Sidi Toui National Park, Tunisia. A total of 417 active latrines were recorded across 67 surveyed quadrats, with significant clustering in specific areas indicating selective habitat use. Spatial analysis revealed autocorrelation across seven distance classes, with Moran's I values ranging from a significant positive value (0.326, p < 0.001) at the smallest distance class (0–1500 m) to a return of clustering at the broadest scale (0.176, p < 0.001) after a phase of non‐significant or negative autocorrelation between 2500 and 6000 m, reflecting a multi‐scale spatial structure characterised by alternating clustering and dispersion. These findings highlight a non‐random, structured spatial pattern influenced by environmental, spatial and anthropogenic factors. Multi‐model inference identified gazelle abundance, predator abundance and topography as the primary predictors of latrine site selection, with plains and hills being particularly favoured. Secondary influences included man‐made features. These findings offer actionable insights for conservation, suggesting that future management strategies should prioritise the preservation of open habitats, ensure reliable access to water sources and minimise human disturbance in critical areas to support the spatial behaviour and ecological requirements of dorcas gazelles.